Histologic chorioamnionitis is associated with reduced risk of late-onset sepsis in preterm infants - Strunk, T.; Doherty, D.; Jacques, Angela; Simmer, K.; Richmond, P.; Kohan, R.; Charles, A.; Burgner, D. (American Academy of Pediatrics, 2012)
BACKGROUND: Histologic chorioamnionitis (HCA) is implicated in the onset of preterm labor and delivery. Chorioamnionitis is a known risk factor for early-onset sepsis and may modulate postnatal immunity. Preterm infants are at greatly increased risk of late-onset sepsis (LOS), particularly with coagulase-negative staphylococci (CoNS), but the impact of HCA on the risk of LOS is unknown. METHODS: Eight hundred thirty-eight preterm infants born at <30 weeks gestational age at a single tertiary center were included. Histologic examination of placenta and extraplacental membranes was performed, and clinical data were extracted from hospital databases. The influence of HCA on the incidence of early-onset sepsis and LOS was examined using logistic regression analysis and Cox proportional hazards regression. RESULTS: Mean gestational age was 26.9 +/- 1.9 weeks, and mean birth weight was 936 +/- 277 g. Two hundred and seventy-six (33%) of 838 infants developed LOS. The presence of fetal or maternal HCA, or maternal HCA and fetal HCA alone, was associated with a significantly decreased risk of LOS with any organism. Histologic chorioamnionitis correlated with a significantly decreased risk of CoNS LOS. CONCLUSIONS: HCA is associated with a significantly reduced risk of acquiring LOS, both with CoNS and other bacteria. Perinatal inflammation may enhance the functional maturation of the preterm immune system and provide protection against LOS in high-risk preterm infants.